2024
DOI: 10.1108/jabs-01-2023-0007
|View full text |Cite
|
Sign up to set email alerts
|

Examining the influence of functional value, social value and emotional value on purchase intention for tires in Japan

Jia Wells,
Caroline S.L. Tan

Abstract: Purpose This study aims to examine the relationships between functional value (quality and price), social value (extrinsic and intrinsic), emotional value and attitude toward a brand, as well as the direct relationship between attitude toward a brand and the purchase intention of tires. This research also explores the moderating effect of social influence on the relationship between attitude toward a brand and purchase intention. Design/methodology/approach A conceptual model based on literature is developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…That is, when he/she becomes aware of his/her health, then repurchase behavior comes from this, which refers to a scenario where the consumer reduces his/her susceptibility to consider alternative products due to the attachment that has been created [74]. Under this same context and to support the findings of this study, a recent study has been identified that refers to the health-conscious consumer as that character who associates a healthy product with emotional value, and that is that when a consumer believes in a product, and it meets their expectations of health and well-being, an emotional relationship is generated, the same one that derives from a pleasant experience [75,76].…”
Section: Discussionsupporting
confidence: 68%
“…That is, when he/she becomes aware of his/her health, then repurchase behavior comes from this, which refers to a scenario where the consumer reduces his/her susceptibility to consider alternative products due to the attachment that has been created [74]. Under this same context and to support the findings of this study, a recent study has been identified that refers to the health-conscious consumer as that character who associates a healthy product with emotional value, and that is that when a consumer believes in a product, and it meets their expectations of health and well-being, an emotional relationship is generated, the same one that derives from a pleasant experience [75,76].…”
Section: Discussionsupporting
confidence: 68%